Proses Densifikasi Pelepah Sawit Menggunakan Gliserol Sebagai Filler Menjadi Bahan Bakar Padat - Jimmy Anderson; Zuchra Helwani; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm frond has been utilized only for raw source of animal feed, compost and organic fertilizer in plantation area. Oil palm fronds has calorific value of 15,184.05 kJ/kg with a density of 0.1383 g/cm3. Calorific value can be enhanced by densification. By biomass densification aims to increase density and decrease handling issue such as storage and transportation. The aims of this research is to produce solid fuel from palm fronds by densification process, to determine the characteristics of the product and to know the effect of gliserol as filler composition and pressing pressure in the processing by densification and also to know density, calorific value and proximate of product. The composition of gliserol filler used were 15%, 25% and 35%. Pressing pressure used were 50, 75 and 100 bar. The particle size used were < 850 μm. The highest density of the product is 1.07475 gr/cm3 was obtained at gliserol filler composition 35% and pressure 100 bar. The highest calorific value of the product is 16,928.12 kJ/kg was obtained at gliserol filler composition 35% filler and pressure 100 bar. The most affecting factor to caloric value and density are pressing pressure and filler composition.Keywords: calorific value, densification, density, filler, pressing pressure, palm fronds.